Muuttuvat suomalaiset äänimaisemat - Ruohonen, Kaisa; Uimonen, Heikki; Kytö, Meri (Tampere University Press, 2017)
Muuttuvat suomalaiset äänimaisemat (Transforming Finnish Soundscapes, eds Heikki Uimonen, Meri Kytö & Kaisa Ruohonen) is a collection of research essays and texts that study the sonic environment and how it is experienced. Soundscapes related to time, place and the everyday shape our perception of the present and the past. Sounds can be pleasant and beautiful, pacing the day or year, annoying, boring and everything in between. The theme of transforming soundscapes combines the research essays in the publication. The essays draw from various disciplines and methodologies: media studies, anthropological field work and sensory observation, textual analysis and close reading, folkloristics, archeoacoustics and music studies. In turn, the texts gathered via a writing competition show how sounds can be listened to both analytically and aesthetically, connecting them to local, national and transnational cultures and histories pondering what sounds mean to the listeners and how they influence the soundscape they live in. The study is a revisit to the One Hundred Finnish Soundscapes project (2006).